2021
DOI: 10.1186/s12933-021-01337-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heart rate variability (HRV) in subjects with type 2 diabetes mellitus with and without diabetic foot: correlations with endothelial dysfunction indices and markers of adipo-inflammatory dysfunction

Abstract: Background Some studies have suggested that patients with diabetes and foot complications have worse cardiovascular and cerebrovascular risk profiles, higher degrees of endothelial dysfunction and arterial stiffness and a higher inflammatory background than patients with diabetes without diabetic foot complications. Patients with diabetes mellitus have an alteration in the sympathovagal balance as assessed by means of heart rate variability (HRV) analysis, which is also related to the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…It may be possible that dyslipidaemia may negatively affect the myelination status of the nerves, and thereby, it may cause dysregulation of ANS. [17,18] AIP index was also positively associated with CSBP and baPWV, which are non-invasive surrogate markers of arterial stiffness. Understandably, enhanced atherogenicity of plasma may escalate arterial stiffness.…”
Section: Discussionmentioning
confidence: 91%
“…It may be possible that dyslipidaemia may negatively affect the myelination status of the nerves, and thereby, it may cause dysregulation of ANS. [17,18] AIP index was also positively associated with CSBP and baPWV, which are non-invasive surrogate markers of arterial stiffness. Understandably, enhanced atherogenicity of plasma may escalate arterial stiffness.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, omentin could ameliorate doxorubicin-induced H9c2 cell apoptosis [ 9 ]. Similarly, most cross-sectional studies reported that the circulating omentin1 levels were lower in patients with ischemic stroke, metabolic syndrome, or type 2 diabetes compared with subjects without cardiovascular diseases [ 10 12 ]. All of these are consistent with observations from several studies that omentin1 levels were inversely associated with multiple cardiovascular risk factors including BMI, age, waist circumference, insulin resistance, glucose levels, and lipid levels [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the articles reviewed herein, five showed differences in RH between healthy subjects and diabetic patients with and/or without neuropathy [15,30,33,57,58], while one study did not show such differences between healthy subjects and diabetic patients, but patients with diabetic ulcers had lower RH index values compared to healthy controls [59]. Another study found no significant difference in blood flow after a muscle strain that induced reactive hyperemia (PSRH) between normal subjects and diabetic non-smokers [43].…”
Section: Resultsmentioning
confidence: 78%
“…Nine studies (Table 2) compared reactive hyperemia between diabetic patients with and without CAN [15,20,30,43,[58][59][60][61][62]. Four of them measured reactive hyperemia using PAT [15,59,61,62], and only two found a significantly lower endothelial-function-derived measure of PAT in diabetic patients with CAN than in those without CAN [15,59]. Four studies measured reactive hyperemia using FMD.…”
Section: Hrv (Cv Of Rr Intervals)mentioning
confidence: 99%
See 1 more Smart Citation